Responsibility of Criminals for Abuse of Visit Visa Exemptions in The Working Area of The TPI Makassar Class 1 Immigration Office - Mustakim Tenreng; Sufirma Rahman; Baharuddin Badaru (JURNAL HUKUM SEHASEN, 2024)
This research was conducted with the aim of: (1) knowing and analyzing the forms of accountability and law enforcement regarding misuse of free visit visas that occur in the working area of the TPI Makassar Class 1 Immigration Office; (2) knowing and analyzing the factors that influence law enforcement regarding misuse of free visit visas in the working area of the TPI Makassar Class 1 Immigration Office. The research method in this research uses empirical research type. Data collection techniques were carried out through interviews and distributing questionnaires. Data were analyzed using descriptive analysis methods using the theory of legal effectiveness as the analytical tool for this research. The results of this research show that: (1) Forms of accountability and law enforcement for misuse of free visit visas that occur in the working area of the TPI Makassar Class 1 Immigration Office are carried out in two ways, namely administrative actions in the Immigration sector and Pro Justisia actions. At the TPI Makassar Class I Immigration Office, immigration cases more often occur, the handling of which is resolved by administrative action in the Immigration sector; (2) Factors that influence law enforcement regarding misuse of free visit visas in the working area of the TPI Makassar Class 1 Immigration Office, namely; legal factors, law enforcement factors, facilities and infrastructure factors, community factors, and legal culture